$c$-quasi $(τ_1,τ_2)$-continuous multifunctions (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concepts of upper and lower $c$-quasi $(τ_1,τ_2)$-continuous multifunctions. Moerover, several characterizations of upper and lower $c$-quasi $(τ_1,τ_2)$-continuous multifunctions are established.
Keywords: $τ_1τ_2$-open set; upper $c$-quasi $(τ_1,τ_2)$-continuous multifunction; lower $c$-quasi $(τ_1,τ_2)$-continuous multifunction